Lattice Compatibility Theory LCT investigations on sulfur-oxygen substitution during Sb2S3-Sb2O3 crystals growth. (6th March 2015) - Colantoni, A; Longo, L; Boubaker, K; Monarca, D; Cecchini, M; Cividino, S; Yumak, A; Biondi, P; Di Giacinto, S; Menghini, G
Abstract: In this paper, we try to give a plausible explanation to the dynamics of incorporation of sulfur element inside antimony (Sb2 S3 ) lattices. This incorporation has been recorded recently as a possible way for enhancing energy conversion devices performance. Some parameters, such as Urbach tailing, Faraday effect (FE) and Amlouk-Boubaker opto-thermal expansivity constants have been reported and correlated to crystallite size along with conversion performance. It has been demonstrated that lattice-linked parameters' ratio compatibility can be introduced as a guide to explain the increase of the thickness-induced oxygen/sulfur substitution effect which favors such compounds' renewable energy conversion-related properties.